2008
DOI: 10.1002/bsl.842
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of risk assessment instruments in the prediction of impulsive versus predatory aggression

Abstract: Actuarial violence risk assessments, many of which include the construct of psychopathy, have been shown to be superior to clinical judgment in the prediction of long-term risk of community violence and recidivism. While these instruments initially appeared to provide similarly accurate judgments of risk of institutional aggression, recent research has indicated that such assessments may be less robust in this setting. One explanation may lie in the types of aggression most frequently observed in each setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 48 publications
5
41
1
Order By: Relevance
“…In their results, Cornell and colleagues reported that Factor 2 correlated with predatory violence. More recent studies suggest that interpersonal features of psychopathy in particular may predict predatory aggression (i.e., controlled aggressive behavior undertaken to achieve a specific goal or outcome) specifically (e.g., Laurell, Belfrage, & Hellström, 2010;McDermott, Quanbeck, Busse, Yastro, & Scott, 2008;Vitacco et al, 2009;Walsh, Swogger, & Kosson, 2009). For example, McDermott, Quanbeck and colleagues reported that the Interpersonal facet of the PCL-R was moderately predictive of prospective incidents of predatory aggression (AUC = .67) among 238 forensic inpatients over an extensive follow-up period.…”
Section: Components Of Psychopathy and Interpersonal Aggressionmentioning
confidence: 95%
“…In their results, Cornell and colleagues reported that Factor 2 correlated with predatory violence. More recent studies suggest that interpersonal features of psychopathy in particular may predict predatory aggression (i.e., controlled aggressive behavior undertaken to achieve a specific goal or outcome) specifically (e.g., Laurell, Belfrage, & Hellström, 2010;McDermott, Quanbeck, Busse, Yastro, & Scott, 2008;Vitacco et al, 2009;Walsh, Swogger, & Kosson, 2009). For example, McDermott, Quanbeck and colleagues reported that the Interpersonal facet of the PCL-R was moderately predictive of prospective incidents of predatory aggression (AUC = .67) among 238 forensic inpatients over an extensive follow-up period.…”
Section: Components Of Psychopathy and Interpersonal Aggressionmentioning
confidence: 95%
“…High levels of impulsivity have been associated with violent or aggressive behaviour toward others (Berkowitz, 2008;Edwards, Scott, Yarvis, Paizis, & Panizzon, 2003;Fehon, Grilo, & Lipschitz, 2005), and many researchers classify or define violent behaviours as being either intentional and calculated or primarily impulsive in nature (Baratt, Stanford, Kent, & Felthous, 1997;McDermott, Quanbeck, Busse, Yastro, & Scott, 2008); thus, impulsivity may play an central role in the perpetration of some violent behaviours. In addition, in several well-validated and frequently used guides for assessing risk for violence (e.g., HCR-20; Webster et al, 1997), impulsivity is included as a stand-alone item, and therefore independently contributes to the overall risk assessment and prediction of risk for future violence.…”
Section: Individual Factorsmentioning
confidence: 99%
“…, McDermott et al . ). However, these tools are characterised by a relatively low number of items and a limited capacity to capture idiosyncratic warning signs typical of the individual patient.…”
Section: Introductionmentioning
confidence: 97%